Survei Pembinaan Prestasi Sepak Bola pada Sekolah Sepak Bola (SSB) di Kota Magelang Tahun 2021 - Manan, Muhammad Fathur Ro'ufil; Yuwono, Cahyo (Universitas Negeri Semarang, 2023)
The survey of soccer achievement development at the soccer school (SSB) in the city of Magelang in 2022 used a qualitative research type, in which efforts were made to explore and understand the meaning of what happened to various individuals or groups stemming from social or humanitarian issues. The results showed that the implementation of achievement development in terms of several aspects such as training programs, sources of SSB funds, mass processing, nurseries, facilities and infrastructure and achievements were quite good. The coaching process has been carried out according to the level of development. In terms of organization, all three have organizational tools and have carried out their duties well. The coach as an organizational device also carries out his duties well and makes training programs that are grouped according to the athlete's age and include technical, physical and mental training. In addition, funding is also well managed and well distributed for the procurement of facilities and infrastructure. However, there is a need for improvement in several aspects in order to increase athlete achievement.